ANALYZING PATTERNS OF CONGRATULATORY STRATEGIES IN VIETNAMESE FACEBOOK WEDDING ANNOUNCEMENTS - Do Thanh Hien Le; Vien Truong (Tạp chí Khoa học Đại học Đà Lạt)
This study explores the patterns of congratulatory strategies related to wedding rituals on Facebook, a prominent platform within the Vietnamese community. With the increasing integration of information technology, Facebook has become a vital space for expressing emotions and fostering connections. Employing a descriptive research design, the study integrates both quantitative and qualitative approaches to data analysis. Quantitatively, the frequency of semantic formulas used in congratulatory messages was calculated and compared across engagement and wedding announcements, with descriptive statistics applied to interpret the data. Qualitatively, an ethnographic approach was used to explore and analyze these strategies through observation and discourse analysis, identifying recurring themes and patterns. The analysis reveals seven distinct patterns, including two single-strategy patterns–using illocutionary force indicating devices (IFIDs) and offering good wishes–and five combined-strategy patterns that integrate IFIDs with offering good wishes, giving compliments, joking, and expressing positive emotions. These findings highlight linguistic and cultural features that showcase how Vietnamese users express care, pleasure, and affection in congratulatory comments, reflecting the preservation of cultural traditions in a digital context. This study contributes to the sociolinguistics field by providing insights into the intersection of social media and cultural expression, offering a novel perspective on Vietnamese culture in online communication. While the study is limited by the availability of data specific to Facebook wedding announcements, its findings offer valuable implications for understanding the role of social media in shaping and sustaining cultural practices.